2020
DOI: 10.1038/s41598-020-70886-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA EIF3J-AS1 enhanced esophageal cancer invasion via regulating AKT1 expression through sponging miR-373-3p

Abstract: Esophageal cancer (ECa) remains a major cause of mortality across the globe. The expression of EIF3J-AS1 is altered in a plethora of tumors, but its role in ECa development and progression are undefined. Here, we show that EIF3J-AS1 is up-regulated in ECa and that its expression correlates with advanced TNM stage (P = 0.014), invasion depth (P = 0.001), positive lymph node metastasis (P < 0.001) and poor survival (OS: P = 0.0059; DFS: P = 0.0037) in ECa. Functional experiments showed that knockdown EIF3J-AS1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In recent years, an increasing number of studies have shown that the dysregulation of lncRNAs, such as lncRNA MALAT1 and DRAIC, plays important roles in the initiation and development of PCa [17][18][19][20]. LncRNA EIF3J-AS1 was found to function as an oncogene in different kinds of cancer [8,10] and to induce chemoresistance [21]. However, the role of EIF3J-AS1 has not been described with regard to PCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing number of studies have shown that the dysregulation of lncRNAs, such as lncRNA MALAT1 and DRAIC, plays important roles in the initiation and development of PCa [17][18][19][20]. LncRNA EIF3J-AS1 was found to function as an oncogene in different kinds of cancer [8,10] and to induce chemoresistance [21]. However, the role of EIF3J-AS1 has not been described with regard to PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNA EIF3J antisense RNA 1 (EIF3J-AS1) was found to function as an oncogene in glioma, colorectal cancer, esophageal cancer, etc. [8][9][10], demonstrating its clinical potential as a biomarker and therapeutic target. However, the role of EIF3J-AS1 in PCa remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…ZFAS1 was validated to be directly targeted by miR-373-3 p . Actually, miR-373-3 p was found to inhibit cancer development through targeting different lncRNAs [ 17 , 18 ]. Here, miR-373-3 p functioned as a tumor suppressor miRNA in TPC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal and uncontrolled cell proliferation is a hallmark of cancer, and is caused by the misregulation of the expression of various crucial molecules. Although numerous oncogenes, tumor suppressor genes, and tumor-related signaling pathways have been identified and confirmed in recent years, the pathogenesis of EC remains unclear (24)(25)(26). In total, 18% of ncRNAs are associated with human tumors, while lncRNAs account for 9%, suggesting that lncRNAs may be a major factor in carcinogenesis and cancer progression (27).…”
Section: Discussionmentioning
confidence: 99%